Reassessing the impact of the Pantawid Pamilyang Pilipino program: Results of the third wave impact evaluation - Aniceto C. Orbeta; Kris Ann M. Melad; Nina Victoria V. Araos (Philippine Institute for Development Studies (PIDS), 2021)
The Pantawid Pamilyang Pilipino Program (Pantawid Pamilya) remains the main social protection strategy of the government with its objective of breaking the intergenerational transmission of poverty by helping poor households invest in the health and education of their children. Previous impact evaluation studies of the program show that the program has been successful in keeping children healthy and in school. The third impact evaluation (IE Wave 3) aims to reassess the program's impact on short-term and intermediate outcomes on health, education, household welfare, and other sociobehavioral domains. The 3rd wave evaluation employs regression discontinuity design (RDD) to analyze program impact by comparing treatment (Pantawid beneficiaries) and comparison households (non-Pantawid beneficiaries) within specific bandwidths of distance from the poverty thresholds that determine program eligibility. In general, the results of the evaluation indicate that the program still shows desirable impacts on most of the target education and health outcomes of children and pregnant women. The results also show positive impacts on household welfare such as income and food security; large positive impacts on community participation, and awareness of basic means to mitigate vulnerabilities such as disaster preparedness among adults; and a strong impact on "grit" or determination of children. Nevertheless, some of the results are inconsistent with previous evaluations such as the negative impact on some nutrition outcomes, inconsistencies in the utilization of maternal health care services, and lack of significant reduction in child labor incidence. Recommendations put forward include strengthening and improving program monitoring and enforcement of health conditions, further study on the factors driving some of the unexpected results, the corresponding adjustment in the policies or incentives that the program provides - particularly in terms of reevaluating the value of the cash grant and taking advantage of the positive program impacts on the behavior of children and adults as a model and/or platform for other interventions.
Keywords: 330; Pantawid Pamilya; 4Ps; Cash transfers; human capital; Regression Discontinuity; impact evaluation